TFG::MET-rearranged soft tissue tumor: A rare infantile neoplasm with a distinct low-grade triphasic morphology - Michal, Michael; Ud Din, Nasir; Švajdler, Marián; Klubíčková, Natálie; Ptáková, Nikola; Hájková, Veronika; Michal, Michal; Agaimy, Abbas (Genes, chromosomes & cancer, 2023)
This article presents 2 cases of TFG::MET-rearranged mesenchymal tumor, an extremely rare molecular subset among an emerging group of mesenchymal neoplasms with kinase gene (NTRK, BRAF, RET and others) alterations. Both tumors were congenital, occurred in female patients and presented as huge masses on the trunk and thigh, measuring 18 and 20 cm in the largest dimension. Both cases showed identical areas with a distinctive triphasic morphology resembling fibrous hamartoma of infancy (FHI), consisting of haphazardly arranged ovoid to spindled cells traversed by variably cellular and hyalinized fascicles admixed with (most likely non-neoplastic) adipose tissue. In other areas, a high-grade infantile fibrosarcoma/malignant peripheral nerve sheath tumor-like (IFS/MPNST-like) morphology was present in both cases. While the first case co-expressed CD34 and S100 protein, the other case did not. When combined with the three previously reported MET-rearranged cases (of which two harbored TFG::MET fusion), 3/5 and 3/4 of MET-rearranged and TFG::MET fusion-associated tumors, respectively exhibited similar triphasic FHI-like low-grade morphology. This points toward the existence of a relatively distinct morphological subset among kinase-fusion-associated tumors which seems to be strongly associated with MET fusions. It seems some of these low-grade cases may transform into a high-grade variant with IFS/MPNST-like morphology as has been observed in other tumors with kinase gene fusions. While most cases seem to follow an indolent clinical course, the recognition of these tumors is clinically relevant as MET tyrosine kinase inhibitors might represent an effective treatment option for clinically aggressive or unresectable cases.
Keywords: kinase fusion; lipofibromatosis-like neural tumor; fibrous hamartoma of infancy; Skin Neoplasms; proteiny; nádory měkkých tkání; neurofibrosarkom; nádory z pojivové a měkké tkáně; MET rearrangement; Gene Fusion; Biomarkers, Tumor; Fibrosarcoma; ženské pohlaví; nádorové biomarkery; Humans; nádory kůže; mesenchymal; fibrosarkom; fúze genů; Soft Tissue Neoplasms; Neoplasms, Connective and Soft Tissue; Neurofibrosarcoma; congenital; soft tissues; TFG::MET fusion; infantile fibrosarcoma; Female; Proteins; lidé